Evaluation of Etanercept Treatment in Newborn Rat Model with Hyperoxic Lung Injury. (2nd September 2016) - Kaya, Guven; Saldir, Mehmet; Polat, Adem; Fidanci, M. Kursat; Erdem, Aysegul; Erdem, Galip; Kurt, Yasemin Gulcan; Cetinkaya, Merih; Cekmez, Ferhat; Onguru, Onder; Tunc, Turan
ABSTRACT: Background: Many factors contribute to the development of BPD basically by increasing inflammation in preterm lungs. However, premature neonates have insufficient anti-inflammatory capacity. We aimed to evaluate the effect of etanercept, an anti-TNF agent, on BPD development in newborn rat model with hyperoxia-induced lung injury. Methods: Thirty-two newborn rats were divided into 3 groups as control group (Group 1, n = 11), hyperoxia + placebo group (Group 2, n = 10), and hyperoxia + etanercept group (Group 3, n = 11). Histopathological and biochemical analysis were performed in order to assess inflammation and oxidative stress. Superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) activities, and malondialdehyde (MDA) levels were studied, histopathological scoring and radial alveolar count were applied in lung tissue. Lamellar body membrane protein, vascular endothelial growth factor (VEGF), nuclear factor-kappaB (NF-κB) gene expressions were studied in immunohistochemical evaluation of tissue samples. All three groups were compared with each other in terms of all parameters. Results: SOD and GSH-Px activities were significantly higher, whereas MDA levels were lower in group 3, compared to group 2 ( p < 0.001). Histopathological scores were lower, lamellar body membrane protein expression and radial alveolar count were higher in group 3 ( p < 0.05). NF-κB expression was higher in group 2, but lower in group 3 in comparison with group 1. Expression of VEGF was decreased in group 2 but came close to group 1 with etanercept treatment in group 3. Conclusions: We found etanercept treatment to be protective in newborn rats with hyperoxia-induced lung damage.